ROUTLEDGE HANDBOOK OF RESEARCH METHODS IN THE STUDY OF INDIGENOUS RELIGIONS ([S.l.])
1 online resource
Keywords: "Exciting developments in research among, with and by Indigenous scholars and communities are enriching a wide range of disciplines, methodologies, and trans-disciplinary conversations. This growing field offers important insights and provocations about methods and approaches. Indeed, key issues such as relationality, decolonisation, research ethics, pedagogy and collaboration necessarily require improvements both in scholarly description and in scholarly practice. Similarly, key themes for Indigenous people intersect strongly both with recent scholarly "turns", such as embodiment, gender, performance, place, ontology, and materiality. The Routledge Handbook of Research Methods in the Study of Indigenous Religions reflects on appropriate approaches and methods with over 40 chapters by a team of international contributors. The Handbook is divided into three parts: - Core themes and critical issues in research and debate about Indigenous Religions - Disciplines and methods, focusing on ways in which researchers gain and share understanding about Indigenous religions - Recent scholarship about broad regions of the world Within these sections, central issues, debates and problems are examined, including: cosmology, diaspora, bodies and materiality, witchcraft and divination, ritual studies, ethnography and fieldwork, heritage studies, ecology, feminist methodologies, decolonial methods and Indigenist methods, research ethics, activism, health, and peoplehood, kinship and relations. The Routledge Handbook of Research Methods in the Study of Indigenous Religions is essential reading for students and researchers in religious studies and Indigenous studies, the handbook will also be very useful for those in related fields, such as sociology, anthropology, history and politics"--